Defensin: The immune system regulatory factor against peripheral nerve disease - Tiantian Qi; Qi Yang; Haotian Qin; Yuanchao Zhu; Jinyuan Chen; Hongfa Zhou; Jian Weng; Hui Zeng; Fei Yu (Brain-X)
Abstract Peripheral nerve disease is commonly encountered in orthopedics, neurology, and neurosurgery. Due to its large population, a substantial number of patients are affected by these conditions in China. Peripheral nerve disease has a high disability rate and current treatments show poor clinical efficacy, resulting in a heavy burden for patients and the country's healthcare system. Defensins are widespread proteins, commonly found in animals, plants, and fungi, with multiple subtypes able to kill a variety of pathogens. As regulatory factors of the immune system, defensins influence bodily function by participating in inflammatory processes, immune responses, and pathogen resistance; they can affect all stages of nerve conduction and play an important role in lesions of peripheral and effector nerves. This article provides a review of the possible roles and mechanisms of defensins in peripheral nerve disease.